ANALYSIS OF LOAD TRANSFER PLATFORM THICKNESS ON LOAD TRANSFER EFFECTIVENESS AND ROAD STABILITY IN SOFT SOIL - Andrawan, Andrawan; Wijaya, Hendy; Iskandar, Ali; Johan, Albert (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
Reinforcement of road embankments on soft soils is a common challenge in infrastructure projects, especially in conditions of low bearing capacity and large settlement potential. One widely used solution is the pile embankment system with the addition of granular Load Transfer Platform. This study aims to numerically evaluate the effect of variations in LTP quality and thickness on system performance. Modeling was conducted using the two-dimensional finite element method, with variations in CBR values of 40% and 45%, and LTP thicknesses of 1 m, 1.5 m, and 2 m. The parameters analyzed include the amount of embankment settlement, slope safety factor, axial force on piles, and visualization of arching effect. The results showed that increasing the quality and thickness of the LTP was able to reduce embankment settlement and increase the factor of safety, especially under short-term conditions. The axial force on the piles also increased as the stiffness of the LTP increased, although at a certain thickness it was thought that there was more optimal force attenuation. These findings indicate the importance of appropriate LTP configuration in the design of soft soil reinforcement systems. Abstrak Perkuatan timbunan jalan di atas tanah lunak merupakan tantangan umum dalam proyek infrastruktur, khususnya pada kondisi daya dukung rendah dan potensi penurunan yang besar. Salah satu solusi yang banyak digunakan adalah sistem pile embankment dengan penambahan load transfer platform (LTP) berbahan granular. Penelitian ini bertujuan untuk mengevaluasi pengaruh variasi kualitas dan ketebalan LTP terhadap kinerja sistem secara numerik. Pemodelan dilakukan menggunakan metode elemen hingga dua dimensi, dengan variasi nilai CBR sebesar 40% dan 45%, serta ketebalan LTP 1 m, 1,5 m, dan 2 m. Parameter yang dianalisis meliputi besarnya penurunan timbunan, faktor keamanan lereng, gaya aksial pada tiang pancang, serta visualisasi arching effect. Hasil penelitian menunjukkan bahwa peningkatan kualitas dan ketebalan LTP mampu menurunkan penurunan timbunan dan meningkatkan faktor keamanan, khususnya pada kondisi jangka pendek. Gaya aksial pada tiang juga meningkat seiring peningkatan kekakuan LTP, meskipun pada ketebalan tertentu diduga terjadi peredaman gaya yang lebih optimal. Temuan ini menunjukkan pentingnya konfigurasi LTP yang tepat dalam desain sistem perkuatan tanah lunak.